Development of student worksheet based on the creative problem solving model to facilitate mathematical creative thinking skills - Heleni, Susda; Suanto, Elfis; Zunianto, Rizki (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2025)
This research aims to develop a student worksheet based on the Creative Problem Solving (CPS) model to facilitate students' mathematical creative thinking skills on the topic of systems of linear equations in two variables. The development process follows the 4-D model: define, design, develop, and disseminate. During the define phase, problems in current learning resources were identified through interviews and observations. The design phase involved the creation of a worksheet aligned with CPS syntax and learning objectives. In the develop phase, expert validations and student trials were conducted, resulting in a validity score of 91% and a practicality score of 92%, indicating the product is very valid and very practical. The final product was disseminated through seminars and school distribution. The results show that the CPS-based student worksheet is feasible and can serve as an effective learning resource to enhance students' mathematical creative thinking skills.